Synergetic effect as a key aspect of the activity of the united territorial communities - Yu.I. Boyko (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article presents the results of the theoretical investigation of the synergetic effect as an economic category and its provision by the financial and economic relations of the united territorial communities. The decentralizations process determines the creation on the basis of sustainable development of significant benefits through the implementation of cumulative potential. The purpose of the article is to consider the essence and main manifestations of the synergistic effect in the process of decentralization, the key aspects of its statistical evaluation. The united territorial communities today are a sustainable form of internal integration that can provide a synergistic effect development activity. The peculiarities of formation and manifestation of synergistic effect are established. Its appearance as a result of decentralization occurs on the basis of a set of effects under the influence of a set of factors. The approach to estimate the synergistic effect is proposed.